Oxcarbazepine and Hyponatremia - Julija Čiauškaitė; Giedrė Gelžinienė; Giedrė Jurkevičienė (Medicina, 2022)
Background and Objectives: Hyponatremia is one of the most common adverse effects in patients treated with oxcarbazepine (OXC). Different risk factors for OXC-induced hyponatremia have been described as age, female gender, dosage, and combination with other drugs During our clinical practice, we noticed that a longer duration of treatment with OXC could be associated with a higher risk of hyponatremia, therefore, in this study, we aimed to evaluate factors that may increase the risk of OXC-induced hyponatremia. Materials and Methods: Data were retrospectively collected from our clinical database at the Department of Neurology of the Hospital of Lithuanian University of Health Sciences Kaunas Clinics. The sample was divided into three groups: OXC consumers (n = 31), other anti-seizure medications (ASMs) consumers (n = 43), and controls absent ASMs (n = 31). All groups were matched by age and gender. Hyponatremia was defined as <136 mmol/L. Results: The frequency of hyponatremia was significantly higher among OXC patients (61.3%) compared to other ASM patients (5.4%) and controls (3.2%). The mean serum sodium concentration in the OXC group was 133.1 ± 5.1 mmol/L. The frequency of severe hyponatremia among OXC-treated patients was 19.4%; this subgroup was older than patients with moderate hyponatremia and normonatremia and had a longer OXC treatment duration compared to a subgroup of normonatremia. The average duration of OXC therapy was 8.7 ± 5.5 years with a range from 1 to 21 years. Serum sodium concentration and duration of treatment with OXC demonstrated a significant negative correlation (r = −0,427, p = 0.017). Each year of therapy with OXC increased the risk of hyponatremia 1.3 times (OR = 1.326, 95% Cl 1.027–1.712, p = 0.031). Other factors (gender, age, polypharmacy, OXC dosage, and serum concentration) did not show a significant association with the development of hyponatremia. Conclusions: Longer duration of treatment with OXC is an important factor in the development and severity of hyponatremia.